(untitled) - ABDUL GAFFUR B, ARUNACHALAM M (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this paper, Lakshmi the poor mother of seven children lives in an anticipation of good times to live a normal life but living in a new country and new culture made her impossible to seize her needs without any pain. The hypothetical necessity to adapt the new culture, to maintain neighborhood, to chase away the poverty and all such social ethics gave Lakshmi no other way except to accept it. Lakshmi in every twist and turn of the story worked hard to save her children from the degradations like drug, sex, charms over infidelity, the chaos and etc. Every time when the dominant hand falls upon her loved ones to crush them down to earth, Lakshmi emerged in-betweens and tried to confront the influences and she either overcomes or negotiates it. Lakshmi was able to earn employmency, housing, education and the social status in the society for her family only because of her attitude of negotiating the situations or circumstances accordingly.